Exosomes Derived from Mouse Adipose-Derived Mesenchymal Stem Cells Alleviate Benzalkonium Chloride-Induced Mouse Dry Eye Model via Inhibiting NLRP3 Inflammasome - Wang, Guifang; Li, Honghui; Long, Hongmei; Gong, Xileyuan; Hu, Shufang; Gong, Can (Ophthalmic research, 2022)
Purpose: The objective of the study was to investigate efficacy and mechanisms of mouse adipose-derived mesenchymal stem cell-derived exosomes (mADSC-Exos) in the benzalkonium chloride (BAC)-induced mouse dry eye model. Methods: Exosomes in the mADSC culture supernatant were isolated by ultracentrifugation. Western blotting, nanoparticle tracking analysis, and transmission electron microscopy were used to characterize mADSC-Exos. An experimental mouse model of dry eye was established by instillation of 0.2% BAC. mADSC-Exos were administered following BAC treatment. The positive control group was treated with commercial eye drops (0.1% pranoprofen). Corneal fluorescein staining, tear secretion, and tear film break-up time (BUT) were evaluated, and histologic analysis of the cornea and conjunctiva was performed by hematoxylin and eosin and periodic acid-Schiff staining. Apoptosis in the corneal epithelium was detected with the terminal deoxynucleotidyl transferase dUTP nick-end labeling assay and by Western blotting. Levels of pro-inflammatory cytokines in the cornea and conjunctiva were evaluated by flow cytometry, and mRNA and protein levels of NLR family pyrin domain-containing 3 (NLRP3) pathway components were assessed by quantitative real-time PCR and Western blotting, respectively. Results: mADSC-Exos were characterized as vesicles with a bilayer membrane. The particle size distribution peak was at 134 nm. mADSC-Exos specifically expressed cluster of differentiation (CD)9, CD63, and CD81. mADSC-Exos treatment repaired ocular surface damage. Additionally, mADSC-Exos inhibited cell apoptosis, decreased the levels of interleukin (IL)-1β, IL-6, IL-1α, interferon (IFN)-γ, and tumor necrosis factor (TNF)-α, and increased levels of the anti-inflammatory cytokine IL-10. Meanwhile, NLRP3 inflammasome activation and upregulation of caspase-1, IL-1β, and IL-18 were reversed by mADSC-Exos. Conclusions: mADSC-Exos alleviate ocular surface inflammation, suggesting that it is a promising treatment for dry eye.